Investigating the commercial community press: the influence of commercial factors in audience selection by Caxton Community Newspapers - Zigomo, Muchena (My University, 2010)
ABSTRACT This study investigated the extent to which commercial factors, such as the need by newspaper publishers to generate and multiply profits to sustain viability and meet shareholder demands, influenced the selection of communities in Soweto as target audiences by community media publisher Caxton Media in the launch of its Urban News community newspapers series. The research is framed in the context of the growing trend of media commercialism, which has gradually expanded to the previously non-profit community media sector, and looks at how community newspaper publishers have employed various strategies, including targeting the most lucrative and segmented audience markets that are of the most value to advertisers, to maintain and increase profitability. It also examines whether or not community media publishers, while pursuing these profit motives, are able to maintain the thrust of what community media should be and how it should operate. The findings show that despite the perceived ‘normative’ ideals of putting the needs and interests of the community first, commercial factors were the primary factors that Caxton considered prior to the launch of the Urban News community newspapers. Contrary to the hypothesis of this study, it was also found that in a commercial community media setting, profit motives can tie in quite well with the ideals of community media if a link is found between editorial content and advertising content.